Desenvolvimento e validação de metodologia de análise de misturas biodiesel: diesel utilizando cromatografia gasosa-espectrometria de massas Development and validation of a methodology FOR analysis of biodiesel: diesel blends using gas chromatography-mass spectrometry - Rita C. M. Faria; Michelle J. C. Rezende; Claudia M. Rezende; Angelo C. Pinto (Química Nova, 2007)
The aim of this work was to develop and validate a method of analysis of biodiesel:diesel blends using HRGC-MS in SIM mode. The proposed method is applicable to biodiesel from linoleic oils, such as soybean oil. The following results were obtained: linearity over the methyl linoleate concentration range of 250-2500 mg L-1 (R² > 0.999); limits of detection and quantification of 2 and 5 mg L-1, respectively; recovery from 82 to 96% of biodiesel in diesel and repeatability < 2% (RSD). Comparison between two operators showed that it is not necessary the same operator to do the analysis.